Gilded - Book 1 - Meyer, Marissa (New York, NY : Feiwel and Friends, an imprint of Macmillan Publishing Group, LLC, 2021)
"Long ago cursed by the god of lies, a poor miller's daughter has developed a talent for spinning stories that are fantastical and spellbinding and entirely untrue. Or so everyone believes. When one of Serilda's outlandish tales draws the attention of the sinister Erlking and his undead hunters, she finds herself swept away into a grim world where ghouls and phantoms prowl the earth and hollow-eyed ravens track her every move. The king orders Serilda to complete the impossible task of spinning straw into gold, or be killed for telling falsehoods. In her desperation, Serilda unwittingly summons a mysterious boy to her aid. He agrees to help her ... for a price. Love isn't meant to be part of the bargain. Soon Serilda realizes that there is more than one secret hidden in the castle walls, including an ancient curse that must be broken if she hopes to end the tyranny of the king and his wild hunt forever"--
Keywords: Rumpelstiltskin (Folk tale) -- Adaptations; Rumpelstiltskin (Folk tale) -- Adaptations; Blessing and cursing -- Juvenile fiction; Truthfulness and falsehood -- Juvenile fiction; Kings and rulers -- Juvenile fiction; Secrecy -- Juvenile fiction; Good and evil -- Juvenile fiction; Fantasy -- Juvenile fiction; Blessing and cursing -- Fiction; Honesty -- Fiction; Kings, queens, rulers, etc -- Fiction; Secrets -- Fiction; Good and evil -- Fiction; Fantasy; Young adult fiction; Fantasy fiction